Peran perempuan dalam pengelolaan air sebagai sumber kehidupan di Wilayah Pesisir Tegalsari, Sidoarjo - Anastasia, Njo; Hermawan, Surya; Harjanti, Dhyah (Penamas: Journal of Community Service, 2025)
The Community Partnership Empowerment Program for the Delta Samudera Timur Group was carried out in Dusun Tegalsari Dukuh Kupang, Jabon District, Sidoarjo Regency. This activity was implemented to address the clean water crisis caused by brackish water conditions that are not suitable for consumption. The main objective is to improve access to clean and consumable water while also promoting gender equality in coastal communities. Efforts were made through the installation of a brackish water purification system utilizing local materials (ALPAMAL), along with gender-based mentoring that emphasizes the distribution of domestic roles and economic opportunities. The implementation began with a community needs survey, followed by the construction and installation of the purification system, and concluded with an evaluation through post-activity interviews. The results showed that the technology successfully produced clean water for both consumption and household needs. The mentoring also increased men’s awareness and participation in domestic work, while opening new business opportunities for women, such as community-based culinary ventures. This program demonstrates that the combination of environmentally friendly technology and social approaches can serve as a catalyst for improving the quality of life and transforming gender relations in coastal areas.